Statistical literacy and scientific reasoning & argumentation in physicians - Schmidt, Felicitas M. (GMS J Med Educ, 2021)
Objective: Statistical literacy (SL) of physicians, i.e. the ability to use and interpret statistical numbers in the context of science, is an essential prerequisite for risk estimation and communication. Together with scientific reasoning and argumentation (SRA) skills, SL provides the basis for evidence-based practice. Several studies suggest that in medical students both skills are underdeveloped. The aim of the present study was to investigate these skills in practicing physicians and how these skills were acquired. Methods: Data collection in N=71 physicians was conducted online and as paper pencil. SL was assessed with multiple-choice items. SRA skills evidence evaluation and drawing conclusions were measured with a decision scenario. Results: Study results indicated that physicians have medium levels of SL (M=17.58, SD=6.92, max 30 pts.) and SRA (evidence evaluation: M=7.75, SD=1.85, max 10 pts.; drawing conclusions: M=37.20, SD=5.35, max 60 pts.). Skills development via autodidactic learning activities (M=4.78, SD=1.13, range 1-6) was reported significantly more often than development during formal medical education (M=2.31, SD=1.46), t(71)=-9.915, p<.001, or in extracurricular activities (M=3.34, SD=1.87), t(71)=4.673, p<.001. The active involvement in research seemed decisive: The number of publications and time spent in research significantly correlated with SL, r(71)=.355, p=.002; respectively r(71)=.280, p=.018. SRA skills were predicted by the type of MD-thesis, β=-.380, p=.016, and working in research, β=3.355, p=.008. Conclusion: Active involvement in research activities seems to be a very important factor for the development of both SL and SRA skills. The implementation of systematic fostering of these skills during formal medical education seems warranted.